anonymous
  • anonymous
find the general solution y``-5y`-6y=cos x
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
this is a 2nd order linear differential equation. There is a really easy method for solving these things. Do you know of it? You should have been told it in class. Otherwise you can search google and it'll tell you the method.
anonymous
  • anonymous
@guess it is a second order equation it as two parts one general and particular and their sum is the complete solution so for general put y''-5y'-6y=0 and replace y^n by D^n and solve quadratic...............try it:)
anonymous
  • anonymous
@RolyPoly let him solve:)

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
First, find the complementary solution by setting the left side equal to 0. y``-5y`-6y=0 <- homogeneous solution, so, λ^2 - 5λ -6 =0 Solve λ \[y_c = c_1e^{\lambda _1 x} + c_2e^{\lambda _2 x}\] Then, find out the particular solution, try \(y_p = Asinx+Bcosx\) (No guarantee that it works though). Differentiate it and solve the A and B. Then, you get \(y_p\) \[y = y_c +y_p\] @Aperogalics I never intend to give out the answer..
anonymous
  • anonymous
y(h)=c1e^(-x)+c2e^(6x) g(x)=cos x y(P)=a cosx+b sin x >> I stood at the 5A-7B=0 -(5B+7A)=0 Then ??
anonymous
  • anonymous
@RolyPoly @Aperogalics @scarydoor thank you but i need some help
anonymous
  • anonymous
Hmm... Do you mind showing your work for the particular solution?
anonymous
  • anonymous
It's called 'method of undetermined coefficients'. If you're going to be doing differential equations a fair bit, then I recommend this book: http://www.amazon.com/Ordinary-Differential-Equations-Dover-Mathematics/dp/0486649407/ref=sr_1_1?ie=UTF8&qid=1354192173&sr=8-1&keywords=ordinary+differential+equations It's about the best book you can get for it.
anonymous
  • anonymous
Do you know how it works? The method to find a particular solution? That seems to be what you're stuck on. This is the method to use: http://en.wikipedia.org/wiki/Method_of_undetermined_coefficients
anonymous
  • anonymous
Of course @RolyPoly y(P)=a cosx+b sin x y`=-A sin x+b cos x y``=a cos x-b sin x y``=-y -y-5y`(-a sin x+b cos x)-6y =cos x 5asinx-5b cos x-7acosx -7b sin x=cos x (5a-7b)sinx-(5b+7a)cos x=cosx 5A-7B=0 -(5B+7A)=0
anonymous
  • anonymous
@scarydoor thanks
anonymous
  • anonymous
y`=-A sin x+b cos x Isn't y'' = -Acosx - Bsinx?
anonymous
  • anonymous
But that doesn't affect your conclusion that y'' = -y y(P)=a cosx+b sin x y`=-A sin x+b cos x y``=-a cos x-b sin x = -y So, -y-5y`-6y =cos x -7 y - 5y' =cos x (5a-7b)sinx-(5b+7a)cos x=cosx 5a-7b=0 -(5b+7a)=0 (it should be -(5b+7a) =1?!)
anonymous
  • anonymous
When you get the two equations: 5a-7b =0 and -(5b+7a) =1 , you can solve a and b and you'll get the particular solution.
anonymous
  • anonymous
@RolyPoly no maybe -5b-7a
anonymous
  • anonymous
(5a-7b)sinx-(5b+7a)cos x=cosx Compare the terms on the left and right, there is no sinx term, so the coefficient of sinx is 0 Hence you get the first equation 5a-7b =0 there is a cosx term, with the coefficient 1, so the coefficient of cosx term on the left is equal to 1. Hence we should get -(5b+7a) = 1 as the second equation. Got it?
anonymous
  • anonymous
@RolyPoly yes thank you so we get a=7/74 b=5/74 ?
anonymous
  • anonymous
Not quite.
anonymous
  • anonymous
You've missed a negative sign for both a and b...
anonymous
  • anonymous
@RolyPoly thank you
anonymous
  • anonymous
Welcome :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.